Combined Epidermal Growth Factor Receptor and Beclin1 Autophagic Protein Expression Analysis Identifies Different Clinical Presentations, Responses to Chemo- and Radiotherapy, and Prognosis in Glioblastoma. (3rd March 2015) - Tini, Paolo; Belmonte, Giuseppe; Toscano, Marzia; Miracco, Clelia; Palumbo, Silvia; Pastina, Pierpaolo; Battaglia, Giuseppe; Nardone, Valerio; Butorano, Marie Aimée Gloria Munezero; Masucci, Armando; Cerase, Alfonso; Pirtoli, Luigi
Abstract : Dysregulated EGFR in glioblastoma may inactivate the key autophagy protein Beclin1. Each of high EGFR and low Beclin1 protein expression, independently, has been associated with tumor progression and poor prognosis. High (H) compared to low (L) expression of EGFR and Beclin1 is here correlated with main clinical data in 117 patients after chemo- and radiotherapy. H-EGFR correlated with low Karnofsky performance and worse neurological performance status, higher incidence of synchronous multifocality, poor radiological evidence of response, shorter progression disease-free (PDFS), and overall survival (OS). H-Beclin1 cases showed better Karnofsky performance status, higher incidence of objective response, longer PDFS, and OS. A mutual strengthening effect emerges in correlative power of stratified L-EGFR and H-Beclin1 expression with incidence of radiological response after treatment, unifocal disease, and better prognosis, thus identifying an even longer OS group (30 months median OS compared to 18 months in L-EGFR, 15 months in H-Beclin1, and 11 months in all GBs) (P = 0.0001 ). Combined L-EGFR + H-Beclin1 expression may represent a biomarker in identifying relatively favorable clinical presentations and prognosis, thus envisaging possible EGFR/Beclin1-targeted therapies.